Relationship of Rainfall Intensity with Slope Stability - Mohammad Haziq Rosly; Habib Musa Mohamad; Nurmin Bolong; Noor Sheena Herayani Harith (Civil Engineering Journal, 2023)
The impact of rainfall on landslides is not an uncommon issue worldwide, including in Malaysia. It is a major challenge for geotechnical engineers to ensure the constructed slope is safe and can sustain longer periods of time, including during heavy rainfall. Kota Belud, Sabah, has been selected as the study area to meet the study objectives. Heavy rainfall has been recorded every year within Kota Belud, which has caused a repetition of landslide occurrences within the hilly areas, especially during the monsoon season. Presently, there is no local procedure for determining the rainfall intensity value for slope stability analysis. This study utilized the rainfall intensity value from Hydrology Procedure 26. Seepage analysis conducted shows rainwater infiltration has caused the groundwater level to increase from rainfall starts until 0.5 m below ground level and decrease after rainfall stops, creating fluctuations in the groundwater level during the wet and dry conditions within the wetting front. The factor of safety of the slope shows a decreasing trend, with a reduction of around 27 to 33% after 24 hours of rainfall in conjunction with the changes in groundwater level. However, the factor of safety increased by around 3% from the initial condition after 48 hours. The objective of this study is to identify the factor of safety of a rainfall-induced slope within Kota Belud utilizing the rainfall intensity design limits from Hydrology Procedure 26. Doi: 10.28991/CEJ-SP2023-09-06 Full Text: PDF